(untitled) - Keene, Michael; (1941-...) (Great Britain, 1997)
This text offers a study of Christianity, Islam, Judaism and Hinduism. The book highlights key questions and covers the following topics, among others, for all four religions - history, belief, buildings, celebrations, pilgrimages, rites of passage and holy scriptures.
Keywords: Christianity